Dynamics of Rural Development: Integrative Report - Mario B. Lamberte; Gilberto M. Llanto; Richard L Meyer; Douglas H. Graham (Philippine Institute for Development Studies (PIDS), 1994)
The Dynamics of Rural Development Project attempts to examine the agricultural sector, which recently has been subjected to comprehensive agrarian reform and rural nonfarm enterprises (RNEs). This paper is an integration of the major findings of various studies under the second set of activities, which consist of collection and analysis of primary and secondary data. Analysis of credit impact on RNE performance is conducted using macroeconometric model. In addition, it also discusses the role of rural labor market in the growth of RNEs and analyzes the impact of agrarian reform on credit markets
Keywords: 330; labor market; macroeconometric model; agrarian reform; agriculture sector; financial liquidity; credit market; rural nonfarm enterprise